Non-technical skills for Moroccan physicians: a cross-analysis of student and professor perspectives in Marrakech - Sebbani, Majda; Alami Idrissi, Anas; Mansoury, Ouassim; Adarmouch, Latifa; Amine, Mohamed; Audétat, Marie-Claude (Frontiers in Education, 2026)
IntroductionIn the context of Moroccan medical education reforms toward a competency-based approach (CBA), the integration of non-technical skills (NTS) is imperative. The Faculty of Medicine and Pharmacy of Marrakech initiated a project to develop its competency framework. This study aimed to identify and prioritize NTS for undergraduate medical training from the students' perspective and to submit these results to experts' judgment.MethodsA mixed-methods study was conducted. A qualitative phase identified NTS through semi-structured interviews with 10 medical students selected via purposive and snowball sampling; data were analyzed using thematic content analysis. A quantitative phase prioritized the identified NTS using the Analytical Hierarchy Process (AHP) technique with 10 faculty professors.ResultsThe qualitative analysis revealed 22 NTS categorized into four domains: Communication, Management and Teamwork, Intrapersonal Skills, and Ethics and Professional Values. In the quantitative phase, the AHP prioritization by an expert group ranked Ethics and Professional Values as the most important domain (relative weight: 0.481), followed by Intrapersonal Skills (0.223), Communication (0.165), and Management and Teamwork (0.131). Key sub-competencies included ethics, empathy, and communication with the patient.DiscussionThis study produces a consensus-based, prioritized framework of non-technical skills that emphasizes the paramount importance of adherence to ethics and professional values and of intrapersonal skills. The findings offer a concrete foundation for educational engineering toward implementing the competency-based approach and for adapting professional situations within the local competency framework at the Faculty of Medicine and Pharmacy of Marrakech. They also provide actionable, context-sensitive guidance relevant to integrating NTS into medical curricula in comparable low- and middle-income settings.